(untitled) (GEOmedia, 2009)
OpenStreetMap: the free maps revolution In a scenario where pervasive mapping is paired with strong monopoly on geographic data, the idea of a college student started the OpenStreetMap project. Today more than 190 thousands mappers collaborate in a wiki way to the first free map of the World. Using just free data and free software you can use the map into a web page, import data into a geodatabase, use the map in a car navigation system. What the community achieved by grassroots mapping and by importing existing free data. How the map compares with proprietary ones. The revolution that Google Maps started, will be completed by OpenStreet-Map?